Determinants of educational technology acceptance: an integration of TAM and UTAUT / Hasni Abdullah ... [et al.] - Abdullah, Hasnida; Sahudin, Zahariah; Bahrudin, Nur Zahidah; Bujang, Imbarine; Khalid, Khairi (Universiti Teknologi MARA, 2023)
Nowadays technologies have become in many parts of life more than ever before. One of the major challenges in dealing with various technologies is to implement them in a useful way to improve life quality. Since educational technologies can play a big role in developing both the teaching and learning process, this paper investigates the status of educational technology in selected universities in Malaysia to obtain their specific perception of this area of study. A survey using a questionnaire was conducted to get data on the implementation of educational technology in universities. Based on the result using Partial Least Square-Structural Equation Modelling SmartPLS 3 software, the findings demonstrated that effort expectancy, perceived playfulness, and social influence primarily influenced the students’ acceptance of educational technology. The level of ease and effort to use the technology will encourage the development of education, enjoyment, and encouragement. On the other hand, performance expectancy and self-management learning was found insignificant.